Stereotactic body radiotherapy (SBRT) in oligometastatic ovarian cancer (OMOC): a systematic review and meta-analysis of clinical outcomes and toxicity profiles - Maiorano, Mauro Francesco Pio; Maiorano, Brigida Anna (Frontiers in Pharmacology, 2025)
IntroductionOligometastatic ovarian cancer (OMOC) represents a distinct clinical state with a limited metastatic burden, potentially amenable to local ablative strategies. Stereotactic body radiotherapy (SBRT) has emerged as a promising treatment in this context, offering high-dose precision with minimal toxicity. However, evidence of its role in OMOC remains fragmented.MethodsWe conducted a systematic review and meta-analysis of studies evaluating SBRT in patients with OMOC, focusing on clinical outcomes, including local control (LC), progression-free survival (PFS), overall survival (OS), and grade ≥3 toxicities. Eligible studies were identified through a comprehensive search across PubMed, Embase, Scopus, and Cochrane Library up to March 2025. Data synthesis involved pooled analysis using random-effects models.ResultsEight retrospective or prospective studies, encompassing 594 patients, were included. The majority of patients had received at least two prior lines of therapy. SBRT was delivered to ≤5 lesions, commonly during systemic treatment-free intervals or maintenance with PARP inhibitors. One-year LC ranged from 86.7% to 94.4%, and 2-year LC ranged from 60.9% to 88.9%. Median PFS ranged from 7.4 to 15.0 months, and median OS from 21.0 to 43.0 months. Grade ≥3 toxicities were rare (0%–6.1%), and no treatment-related deaths were reported.DiscussionSBRT demonstrates favorable LC and survival outcomes in selected OMOC patients while maintaining a low toxicity profile, despite current evidence being descriptive and thus to be interpreted with caution. SBRT use during systemic treatment breaks or as a tool to control oligoprogressive disease under maintenance therapy suggests a potential role in extending treatment-free intervals. These findings support SBRT as a valuable component of a multidisciplinary approach to OMOC and underscore the need for prospective, context-specific trials to validate these results.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251161822, identifer CRD420251161822.